Non-habitual wearing of high-heeled shoes increases loading coefficient, stress and forefoot-rearfoot load imbalance in females as revealed by the modified velocity field diagram - Ibeneme Sam; Ekeanyanwu Ann (Sciendo, 2014)
Study aim: To determine the effects of non-habitual wearing of high-heeled shoes on loading coefficient, loading stress and forefoot-rearfoot load imbalance in females